Author Correction: A next-generation tumor-targeting IL-2 preferentially promotes tumor-infiltrating CD8+ T-cell response and effective tumor control - Zhichen Sun (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.